Moderasi Good Corporate Governance terhadap Pengaruh Pajak dan Mekanisme Bonus pada Transfer Pricing di Indonesia - Putri, Ni Putu Wanda Anggeliana; Putri, I Gusti Ayu Made Asri Dwija; Budiartha, I Ketut; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p04, 2022)
This study aims to obtain empirical evidence of the effect of taxes and bonus mechanisms on transfer pricing in Indonesia with Good Corporate Governance as a moderating variable. The research population is non-financial companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used is purposive sampling in order to obtain 450 observational data. The data analysis technique used is Moderate Regression Analysis (MRA). Based on the results of the analysis of tax variables and the bonus mechanism have a positive effect on transfer pricing. Good Corporate Governance is able to moderate the effect of taxes and bonus mechanisms on transfer pricing. Keywords: Transfer pricing; Tax; Bonus Mechanism; Good Corporate Governance.